The Pauline Effect - Strawbridge, Jennifer R. (Jennifer Ruth), 1978- (Berlin : De Gruyter, 2015)
This study offers a fresh approach to reception historical studies of Scripture, utilizing a methodology introduced by scholars of ancient history and focusing on the four most frequently used Pauline pericopes in pre-Nicene writings. Engaging a wide range of primary texts, it traces the contours and overlap between theology and interpretation of Scripture and examines how these particular texts formed early Christians and their writings.
Print version record.
Master record variable field(s) change: 072, 082
Keywords: Bible. -- Criticism, interpretation, etc; Bible; Christian literature, Early -- History and criticism; Christian literature, Early; RELIGION / Biblical Studies / New Testament; RELIGION / Biblical Studies / Paul's Letters; Electronic books; Criticism, interpretation, etc